Post-traumatic stress disorder in women who suffer domestic violence in the city of Cascavel-PR (Research, Society and Development, 2022)
Introduction: Intimate partner violence against women is a complex public health problem. In Brazil, it affects all social classes, acting on a basis of discrimination and abuse on gender, racial, socioeconomic and generational differences, subjugating women to situations such as hunger, torture, humiliation and mutilation. The effects of violence go beyond social and hospital costs, however it primarily affects women's health, with emphasis on mental health. The aim of this study was to investigate the presence of post-traumatic stress disorder (PTSD) symptoms in female victims of intimate partner violence. It is a structured clinical interview and questionnaire on sociodemographic data and health. Expected results: contribute to the implementation of public policies aimed at caring for this population, as well as the implementation of health promotion projects and/or programs.